microRNA: Diagnostic Perspective - Faruq, Omar; Vecchione, Andrea (Frontiers in Medicine, 2015)
Biomarkers are biological measures of a biological state. An ideal marker should be safe and easy to measure, cost efficient, modifiable with treatment, and consistent across gender and ethnic groups. To date none of the available biomarkers satisfy all of these criteria. In addition the major limitations of these markers are low specificity, sensitivity and false positive results. Recently identified, microRNAs are endogenous, evolutionarily conserved small non-coding RNA (about 22-25nt long), also known as micro-coordinators of gene expression, which have been shown to be an effective tools to study the biology of diseases and to have great potential as novel diagnostic and prognostic biomarkers with high specificity and sensitivity. In fact it has been demonstrated that microRNAs play a pivotal role in the regulation of a wide range of developmental and physiological processes and their deficiencies have been related to a number of disease. In addition microRNAs are stable and can be easily isolated and measured from tissues and body fluids. In this review, we provide a perspective on emerging concepts and potential usefulness of microRNAs as diagnostic markers, emphasizing the involvement of specific microRNAs in particular tumor types, subtypes, cardiovascular diseases, diabetes, infectious diseases and forensic test.